The Rhetoric of Righteousness in Romans 3. 21-26 - Campbell, Douglas A. (England : Sheffield Press, 1992)
The importance of Paul's letter to the Romans need hardly be stated; it is still, however, the subject of serious interpretative disputes. One such pivotal and disputed text in Romans is 3.21-26. The actual meaning is a far less settled issue than the shared evaluation of its importance
Keywords: Bible. N.T. Romans -- Criticism, interpretation